PELAKSANAAN PERLINDUNGAN HUKUM KARYA CIPTA SINEMATOGRAFI PADA APLIKASI TIKTOK DI INDONESIA - Geraldine Mumpuni, Jessica (UNES Law Review, 2023)
Intellectual property rights are rights that originated and are born from the creation of a creation. One form of intellectual property rights is copyright, and one form of copyrighted work is cinematography. Cinematography itself is protected by the rights contained in the copyright. Then, as the time evolves, technology also has a function that can distribute a work of cinematography, as for the creators, this also has a negative impact. Some problems that arise are related to the piracy of copyrighted works or the distribution of cinematographic works without a license or permission. Therefore, the author of the journal intends to discuss concerning the efforts that have been made through the existing legal provisions in Indonesia to protect cinematographic copyrighted works for unauthorized distributions, one of which is through Tiktok media. This research was conducted with normative juridical methods, namely conducting literature studies and studies through laws and regulations.